Toxoplasma gondii seroprevalence among pregnant women in Africa: A systematic review and meta-analysis - (:unkn) unknown (My University, 2024)
Background: Toxoplasmosis is a serious endemic zoonotic disease caused by the protozoan parasite Toxoplasma gondii. Toxoplasma infection during pregnancy can result in congenital transmission and serious fetal and neonatal complications. This systematic review and meta-analysis aimed to assess the pooled seroprevalence of T. gondii infection and its determinants among pregnant women in African countries.Methods: All articles reporting the seroprevalence of toxoplasmosis among pregnant women in African countries and published from 2010 to 2023 were searched using various databases. The pooled prevalence of toxoplasmosis was calculated using a random-effect model. The variation between the included studies was assessed using a funnel plot and I2 heterogeneity statistics. To identify the sources of heterogeneity, sub-group analysis was further conducted by country, diagnostic method, and sub-African region. The association of prevalence rates with the socio-economic level and geoclimatic parameters was also explored.Results: In total, 29,383 pregnant women from 60 articles were included for analysis. The pooled T. gondii seroprevalence was 42.89% with high heterogeneity (I2 = 99.4%, P < 0.001). Sub-group analysis revealed variation by country (ranging from 2.62% in Namibia to 80.28% in Congo), diagnostic method used (from 8.66% in studies using a rapid diagnostic test to 55.69% in those using an agglutination test), and sub-African region (from 4.14% in regions of Southern Africa to 53.96 in Central Africa). Cat ownership (OR = 1.58) and the consumption of raw meat (OR = 1.50) and raw vegetables (OR = 1.48) had a statistically significant combined effect on T. gondii seroprevalence. No association was found between T. gondii prevalence and the level of income of the country or geoclimatic parameters.Conclusion: The prevalence of toxoplasmosis infection among pregnant women in Africa is high, particularly in Central and Eastern Africa. The determina
Keywords: African Research